USE OF TGMS LINES FOR TWO LINE RICE HYBRIDS IN PAKISTAN - M. Akhter; S. S. Ali; M. A. Zahid; M. Ramazan (Journal of Animal and Plant Sciences, 2008)
Six Thermosensitive Genetic Male Sterile (TGMS) lines were evaluated for their sterility / fertility behavior. Three stable TGMS lines were used for floral, morphological, agronomic and quality traits to find out commercially useable TGMS lines for two line hybrid seed production. IR73834-21-26-15-25-4 had shortest plant height (63 cm) with minimum number of tillers per plant (8.0). Phenotypic acceptability was highest for IR73834-21-26-15-25-4, therefore, has the potential for commercial utilization in hybrid seed production. During sterility phase, highest temperature ranged between 39.450C in May to 31.620C in October whereas minimum temperature was observed to be 27.640C in May to 21.640C in October. However, critical fertility phase may be observed in last decade of October with maximum and minimum temperatures of 28.50C and 19.570C, respectively. Critical fertility phase may be extended upto first decade of November. Four TGMS lines i.e. IR73827-23-26-15-7, IR73834-21-26-15-25-4, IR75589-31-27-8-33 and IR76761-4-3-17-34-1 showed TGMS behaviour at Kala Shah Kaku. IR68301-11-6-4-4-3-6-6 and IR76753-41-6-34-13 did not produce any seed and remained un productive throughout the growth period. TGMS lines, IR73827-23-26-15-7, IR75589-31-27-8-33 and IR73834-21-26-15-25-4 showed no difference for leaf blade pubescence, leaf blade colour, legule colour, collar colour, apiculous colour and stigma colour. Anther colour was yellow in IR73827-23-26-15-7. This TGMS line also showed green basal leaf sheath colour as compared to light green in other TGMS line. IR75589-31-27-8-33 had erect flag leaf while horizontal in others. Maximum anther length (2.14 mm) and stigma length (2.0 mm) was observed in IR73834-21-26-15-25-4. Turnucate legule was present in IR73827-23-26-15-7 as compared to 2-cleft legule in others. Straw colour short awns were found only in IR73834-21-26-15-25-4 with intermediate panicle type. However, other TGMS lines showed compact panicle type.
Keywords: Two line rice hybrid; TGMS; characteristics